ОСОБЛИВОСТІ ДИНАМІЧНИХ ХАРАКТЕРИСТИК СИСТЕМ РЕГУЛЮВАННЯ ІЗ ОДНОСТОРОННЬОЮ ТА ДВОСТОРОННЬОЮ ШИРОТНО-ІМПУЛЬСНИМИ МОДУЛЯЦІЯМИ - Щербак, Я.В.; Івакіна, К.Я. (Інститут електродинаміки НАН України, Київ, 2023)
The purpose of the article is: to determine the dynamic properties of automatic control systems of  the pulse DC voltage converter with one-way and two-way modulations by studying the influence of the form of the reference signal on dynamic processes in the systems of automatic control of the output coordinate of the converter with widely used proportional (P), integral (I) and proportionally - by integral (PI) regulators. The novelty of the proposed work lies in the determination of the influence of one-sided and two-sided pulse width modulation on the stability and conditions of the process of the finite duration of the automatic control system of the pulse converter of constant voltage. The dynamic characteristics of the system are investigated using impulse models of the pulse DC voltage converter and the use of the Z-transformation mathematical apparatus and simulation modeling. Analytical dependencies were obtained: stability conditions for proportional, integral and proportional-integral regulators; conditions of the process of finite duration of finite duration in a system with an aperiodic link in the load circuit; oscillograms of transition processes that confirm the theoretical results. The practical value lies in the fact that the results obtained in the work provide, during the development of an automatic regulation system with given parameters, the possibility of optimal selection of the type of pulse-width modulation. References 17, figures 15.